Implementasi SHA-256 Dalam Program Verifikasi Originalitas Video Sebelum dan Sesudah Proses Kriptografi - Daniel Surya Wijaya; I Ketut Gede Suhartana (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2024)
This research aims to develop a computer program utilizing the SHA-256 algorithm to compare the authenticity between the original video and the video that has undergone cryptographic processes, particularly during the decryption phase. The program is designed to provide additional verification regarding the success of the decryption process in restoring the video to its original condition. The program development is conducted using the Python programming language. The SHA-256 algorithm is employed to generate hash values for both the original video and the decrypted video. The resulting hash values of the two videos are then compared to evaluate their similarity. The developed program successfully compares the authenticity between the original video and the decrypted video. Through the analysis of hash values using SHA-256, the program concludes whether the decryption process successfully restores the video to its original state or not.